Advanced Bogolyubov model of imperfect bose gas and superfluidity - Bogolyubov, N.N. Jr.; Sankovich, D.P. (Вопросы атомной науки и техники, 2012)
The equilibrium properties of a system of interacting bosons are studied from a microscopic point of view. We calculate the superfluid density in the Bogolyubov model of imperfect Bose gas. The model superstable Hamiltonian is considered. We examine the case of some pair potential and find the estimate for temperature and density in the λ-point. С микроскопической точки зрения изучены равновесные свойства системы взаимодействующих бозонов. Мы вычисляем плотность сверхтекучей компоненты в модели Боголюбова неидеального бозе-газа. Рассмотрен модельный суперстабильный гамильтониан. Мы изучаем случай некоторого парного потенциала и получаем оценку для температуры и плотности в λ-точке. З мікроскопічної точки зору вивчені рівноважні властивості системи взаємодіючих бозонів. Ми обчислюємо густину надплинної компоненти в моделі Боголюбова неідеального бозе-газу. Розглянуто модельний суперстабільний гамільтоніан. Ми вивчаємо випадок деякого парного потенціалу і одержуємо оцінку для температури і густини в λ-точці.